INDUSTRIAL MAINTENANCE INDICATORS: a case study of management of strategic management impacting corporate results in the agricultural equipment industry - Cardoso, Eduardo Vinicius; Regattieri, Carlos Roberto (Revista Interface Tecnológica, 2020)
The industrial scenario requires constant changes and application of technologies not only in the operational area, but also in the management processes. With the arrival of industry 4.0 and the need for reliable machines to guarantee high productivity, management processes must accompany this panorama, seeking continuous improvement in the analysis and strategy development processes. With industrial parks with relevant types and quantities of machines, effective and results-oriented planning is a practice that has been seen with excellence in industries in various branches, including the one that will be addressed in this work: the branch of agricultural equipment production. In order to demonstrate an analysis of the application of the strategic management process through the main maintenance indicators, a case study was carried out in one in the state of São Paulo, revealing the impacts on corporate results.